Fiscal Institutions at the Cantonal Level in Switzerland - Gebhard Kirchgässner (Swiss Journal of Economics and Statistics, 2013)
In this paper, institutions are described which are designed to reach sustainability of public finances in the Swiss cantons. These are on the one hand direct popular rights, the fiscal referendum in particular, which allow citizens to express their fiscal preferences. These are on the other hand debt breaks, i.e. institutions, which prevent expenditure and revenue from drifting apart too much in order to limit possible deficits. Both together, fiscal referenda and debt breaks, allow cantons to perform a sustainable fiscal policy. This also holds and is particularly important for those cantons that are financially weak. That these institutions are successful is not only demonstrated by descriptive analysis but also supported by econometric analyses. Moreover, they also reduce interest payments cantons have to bear for investment expenditure. Thus, with well-designed institutions federal states might even better be able to follow a sustainable fiscal policy than unitary ones.
Keywords: H63; H74; 330; Sustainability; Public Debt; Fiscal Policy; Fiscal Referendum; Debt Brakes